Chemical and physical characteristics of hybrid alkaline cement composite after laser interaction - Park, Sungwoo; Lian, Mang Muan; Lee, Dongkyoung; Pyo, Sukhoon (Journal of Building Engineering, 2023)
This study investigated the resistance of a hybrid alkaline cement composite (HACC) to laser cutting. HACC, synthesized using geopolymer and cement paste, can be useful for rapid construction or repair due to its faster setting and higher compressive strength than cement paste. Also, laser cutting is a recently popular fabrication method because of low dust and noise production as well as fast speed. Although cement paste was proven to enhance the compressive strength of the geopolymer, its effect on the resistance against laser cutting has not been studied. Laser-cutting experiments were performed in this study on HACCs with five different cement paste contents. Thermogravimetric analysis, X-ray diffraction, and scanning electron microscope with energy dispersive microscope were conducted to investigate the structural changes after the laser treatment. Lastly, the microhardness of HACC was measured to reveal the correlation between physical hardness and thermal resistance. The results demonstrate that sodium aluminosilicate hydrate gels can resist laser cutting more than calcium (alkali) aluminosilicate hydrate and calcium silicate hydrate gels because of their chemical and physical characteristics. •The resistance of HACC against laser cutting decreases with cement content.•N-A-S-H gels are subjected to phase transition by laser interaction.•C-S-H and C-A-S-H gels are subject to phase decomposition by laser interaction.•The phases in descending order of microhardness are N-A-S-H gel, C-A-S-H gel, and C-S-H gel.